TAX REVIEW ATAS KEWAJIBAN KOPERASI PEDAGANG PASAR KUMBASARI-BADUNG SEBAGAI PEMOTONG PPH PASAL 21 TAHUN PAJAK 2014 - Nora Tan, Stephanie; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
Kumbasari-Badung Market Trades Coorperative was incorporated since 1981 and was awarded the first rank Marketing Coorperatives Bali Provincial achievement in 2015 and outstanding Marketing Coorperative 2015 based on the Ministry of Coorperative and Small and Medium Enterprises. This achievement encourages Cooperative to improve its quality, include taxation aspects. This research review of the Coorperative tax liability as cutter income tax article 21 in fiscal year 2014 based on PER-31/PJ/2012. The independent variable are the object of income tax article 21, the cost position, non-taxable income, and tax rates. The dependent variable is the income tax payable article 21. The data collection using interviews and documentation. Data analysis technique using comparative descriptive. The research found that the Coorperative has not fulfilled obligations calculate, cut and deposit the income tax payable article 21, while the obligation to report the income tax payable article 21 has been carried out in accordance with PER-31/PJ/2012.
Keywords: tax review, income tax article 21, PER-31/PJ/2012